Penyandang Autisme Yang Berhasil Meraih Gelar Sarjana - Layla Putri Amalya; Anggi Khoiriyyah Putri; Wahyu Aulia Zalsini (CV. ITTC INDONESIA, 2024)
Autism spectrum disorder (ASD) is a developmental disorder characterized by barriers to communication and social interaction as well as repetitive behavior and limited interests. In adulthood, individuals who experience this disorder have difficulty carrying out reciprocal interactions, understanding communication signals and initiating social interactions, thus hampering personal, academic and work functions. However, this was broken by one person with autism who succeeded in obtaining a bachelor's degree from a university. The purpose of this writing is to increase knowledge about autism and hopefully provide motivation for readers. The method used in this research is a literature study which is a written summary that includes articles from journals, books and other documents that define theories and provide information about the past and present to be organized based on topics and documents required.